Pengaruh Tingkat Pemberian Pupuk Bokashi Kotoran Babi Terhadap Pertumbuhan dan Hasil Rumput Setaria (Setaria spachelata) - Kastalani Kastalani; Maria Erviana Kusuma; Herlinae Herlinae; Petra Petra (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
This study aims to determine the effect of pig manure bokashi fertilizer on the growth and yield of Setaria Grass (Setaria spachelata) and to determine the best level of pig manure bokashi fertilizer application that gives the best result on the growth and yield of Setaria. The implementation of this research took place at the practice location of Faculty of Animal Husbandry, Palangka Raya Christian University, Jalan G.S. Rubay Palangka Raya. This study used a completely randomized design (CRD) with 5 treatments and 4 reflications, namely b0 = Pig Manure bokashi fertilizer 0 ton h-1, b1 = Pig Manure bokashi fertilizer 10 ton h-1, b2 = Pig Manure bokashi fertilizer 20 ton h-1, b3 = Pig Manure bokashi fertilizer 30 ton h-1 and b4 = Pig Manure bokashi fertilizer 40 ton h-1. From the result of this study, it can be seen that various levels of pig manure bokashi fertilizer applications have a significant effect on the number of tillers of Setaria grass 6 mst but not effect plant height and production of Setaria grass. Key words: Setaria grass, Bokashi, pig manure